External and Internal Factors Influencing University Transfer Students and College Life Satisfaction, with Consideration of the Population Problem in Japan (Global Journal of Human-Social Science, 2018)
Since many universities in Japan have tended to admit transfer students in recent years, this paper has discussed to support the design of support services for transfer students. The primary purpose of the study is to explore differences in background characteristics (i.e., parental education level) and examine to what degree internal and external factors affect transfer students' and non-transfer students' college decision-making process. The second purpose is to examine student satisfaction with the quality of campus life post-transfer, as compared to non-transfer students' campus life experiences. The target population was current transfer students in Japanese universities as compared with non-transfer students. 279 college students responded to this survey. Of the 279 students, 110 were transfer students from vocational colleges that teach foreign languages and general education, 83 were transfer students from technical colleges, and 86 were non-transfer students from private universities. My findings reveal that there is a significant difference in parental education among the three groups. The majority of transfer students from vocational colleges were first-generation college students, while most transfer students from technical colleges and non-transfer students were non-first generation college students.
Keywords: transfer student; higher education; parental education; college access; campus life; Japanese education system